Analysis of the constitutional right to health in the Brazilian prison system in times of pandemic (Research, Society and Development, 2021)
This article aims to analyze how the constitutional right to health is being implemented in the context of the Covi-19 pandemic in the prison system. In Brazil, there is an exponential growth of the prison population that has been repeated year after year, which has caused a major collapse in the prison system, and at the same time this has generated neglect by the authorities as a result of the various violations that take place daily within the prisons mainly with regard to the right to health in this pandemic period. From the emergence of the virus contagion, having as its main measure the social isolation and personal hygiene care, the concern arose to know how these measures would be achieved within an environment of degrading conditions such as Brazilian penitentiaries. To carry out this study, the method of deductive procedure, bibliographical research of a qualitative nature and the use of documentary research were used. From the research it was concluded that the pandemic was aggravated by the precariousness that already exists in prisons, such as overcrowding, lack of structure, unhealthy environment and lack of multidisciplinary medical teams to assist in the medical care of prisoners. It is noticed that even with the creation of policies for the realization of the inmates' right to health, they are not put into practice and, in turn, it is necessary that strategies be created so that a positive provision of the state is provided in Brazilian prisons. mainly in this period  pandemic.